Pengaruh Kualitas Pelayanan, Fasilitas, Dan Harga Terhadap Kepuasan Menginap Di Hotel Selecta Kota Batu - Dwi Nawangwulan; Ike Ike; Tri Tri (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Hotel Selecta is one of the oldest hotels in Batu City, originating from the Dutch colonial era, established in 1928 and renovated in 1950 due to damage following Indonesia’s independence. Hotel Selecta is part of an integrated area that includes Selecta Recreational Park and a restaurant, which to this day continues to compete amid the intense tourism competition in Batu City. Batu City is a major tourist destination offering a wide range of accommodation options with various facilities and classifications, including star-rated hotels, budget hotels, and villas. This study aims to analyze the effect of service quality, facilities, and price on guest satisfaction at Hotel Selecta Batu City. Customer satisfaction is a crucial factor in the hospitality industry as it influences customer loyalty and business sustainability. This research employs a quantitative method using a survey approach. Primary data were collected through questionnaires distributed to guests who had stayed at Hotel Selecta Batu City, with the sampling technique using purposive sampling. Data analysis was conducted using multiple linear regression analysis to determine the effect of each independent variable on the dependent variable. The results indicate that service quality has a significant effect on customer satisfaction. Facilities also have a significant effect on customer satisfaction. However, price does not have a significant effect on guest satisfaction. Simultaneously, service quality, facilities, and price have a significant effect on guest satisfaction at Hotel Selecta Batu City. Among these variables, service quality is the most dominant factor influencing guest satisfaction. This study is expected to contribute to the management of Hotel Selecta Batu City by providing insights into improving guest satisfaction through enhanced service quality, adequate facilities, and pricing strategies aligned with customer expectations.